Vanillin Activates Human Bitter Taste Receptors TAS2R14, TAS2R20, and TAS2R39 - Morini, Gabriella; Winnig, Marcel; Vennegeerts, Timo; Borgonovo, Gigliola; Bassoli, Angela (Frontiers in Nutrition, 2021)
Vanilla is widely used in food preparation worldwide for its sensory properties, mainly related to its fragrance, being vanillin the major compound present in the processed vanilla. Vanillin is also known to elicit bitterness as a secondary sensory sensation, but the molecular mechanism of its bitterness has never been reported. Assay buffers of vanillin were tested in vitro on all twenty-five human bitter taste receptors TAS2Rs. Three receptors, TAS2R14, TAS2R20 and TAS2R39, were activated, showing that these receptors are mediating the bitterness of vanillin. The result could be useful to improve the overall sensory profile of this broadly used food ingredient but even more could represent the starting point for further studies to investigate the potential of vanillin in sensory nutrition and other pharmaceutical applications.